Betulinic acid hydroxamate prevents colonic inflammation and fibrosis in murine models of inflammatory bowel disease - Prados María E.; García-Martín Adela; Unciti-Broceta Juan D.; Palomares Belén; Collado Juan A.; Minassi Alberto; Calzado Marco A.; Appendino Giovanni; Muñoz Eduardo (Acta Pharmacologica Sinica, 2021)
Intestinal fibrosis is a common complication of inflammatory bowel disease (IBD) and is defined as an excessive accumulation of scar tissue in the intestinal wall. Intestinal fibrosis occurs in both forms of IBD: ulcerative colitis and Crohn’s disease. Small-molecule inhibitors targeting hypoxia-inducing factor (HIF) prolyl-hydroxylases are promising for the development of novel antifibrotic therapies in IBD. Herein, we evaluated the therapeutic efficacy of hydroxamate of betulinic acid (BHA), a hypoxia mimetic derivative of betulinic acid, against IBD in vitro and in vivo. We showed that BAH (5–20 μM) dose-dependently enhanced collagen gel contraction and activated the HIF pathway in NIH-3T3 fibroblasts; BAH treatment also prevented the loss of trans-epithelial electrical resistance induced by proinflammatory cytokines in Caco-2 cells. In two different murine models (TNBS- and DSS-induced IBD) that cause colon fibrosis, oral administration of BAH (20, 50 mg/kg·d, for 17 days) prevented colon inflammation and fibrosis, as detected using immunohistochemistry and qPCR assays. BAH-treated animals showed a significant reduction of fibrotic markers (Tnc, Col1a2, Col3a1, Timp-1, α-SMA) and inflammatory markers (F4/80+, CD3+, Il-1β, Ccl3) in colon tissue, as well as an improvement in epithelial barrier integrity and wound healing. BHA displayed promising oral bioavailability, no significant activity against a panel of 68 potential pharmacological targets and was devoid of genotoxicity and cardiotoxicity. Taken together, our results provide evidence that oral administration of BAH can alleviate colon inflammation and colitis-associated fibrosis, identifying the enhancement of colon barrier integrity as a possible mechanism of action, and providing a solid rationale for additional clinical studies.